Critical loss analysis in market definition and merger control - Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The last couple of years have seen an increasing interest in critical loss analysis, both, in academia and in practice. This development is documented by various research papers, high-level exchanges between antitrust experts as well as an increasing number of case decisions which make use of some form of critical loss analysis. In this context, it is the aim of this article to describe the general method of critical loss analysis, to assess important properties of the concept, to show how critical loss analysis has to differ between market definition exercises and the evaluation of the competitive effects of horizontal mergers and to discuss applications of critical loss analysis in recent cases. The results suggest that the application of critical loss analysis in practice is often not as straightforward as the rather simple theoretical concept might suggest. In fact, the method has to be applied with great care in order to receive meaningful results.
Keywords: L40; L41; L50; K21; 330; Antitrust; competition policy; market power; market definition; merger control; unilateral effects; Konzentrationspolitik; Fusionskontrolle; Marktmacht; Messung; Relevanter Markt